A massive osteonecrosis with Le Fort I-type pathological fracture, caused by bisphosphonate-related osteonecrosis of the jaw (BRONJ): A rare case report. Issue 3 (May 2016) - Sukegawa, Shintaro; Kanno, Takahiro; Katase, Naoki; Matsuzaki, Hidenobu; Shibata, Akane; Takahashi, Yuka; Furuki, Yoshihiko
Abstract: Bisphosphonates (BPs) are useful drugs for the management of osteoporosis and metastatic bone disease, and are used to prevent skeletal-related events. However, the side effects of BPs, bisphosphonate-related osteonecrosis of the jaw (BRONJ), sometimes severely impairs patient quality of life. Here we report a case of severe BRONJ in the maxilla, which caused Le Fort I-type fracture-like bone fracture due to formation of a large sequestrum in the maxilla.